Perkembangan Kognitif Anak Usia Dini (STPPA Tidak Tercapai) di TK Aisyiah Bustanul Athfal 2 Padangsidimpuan - Mahdi, Nur Imam; Ramadhini, Fitri (IAIN Padangsidimpuan, 2020)
This research is motivated by the low development of cognitive abilities of chidren. This is because teachers still use conventional methods in learning plus family environmental factors that do not support. The purpose of this study is to determine the achievement of cognitive development of SadewaÂ in Class B TK Aisyiah Bustanul Athfal 2 Padangsidimpuan. In this study the subject of the study is a boy aged 5 years 7 months. This research is a qualitative research. The data that the author obtained include interviews with class teachers and parents Sadewa. From the results of the study authors conclude that Sadewa showed extreme cognitive left or low cognitive development